Re-emerging Issue of Bali Strait Connecting Bridge - Eka Ari Suhendra (Bali Tourism Board, 2020)
After received harsh critiques in 2016, once more, a rumor about the construction of a bridge between Java island and Bali island has been sparking wildly since January 2020. Previously, Banyuwangi Regent Azwar anaz proposed a plan to build a connecting bridge to reduce vehicle queues in ketapang harbor. Commonly, the traffic would reach its peak time on holiday season after Eid al-Fitr, where congestion in Ketapang harbor got its limit capacity. For decades, the Bali strait has been serving as a connecting port between Java and Bali, which is essential for economic growth and public migration. Meanwhile, philosophically, the strait holds a symbol of new hope and new life that separates between past and future. A rumor to build an overpass between java island and Bali island discussed in early 2020 and in 2016 to reduce vehicle queues in ketapang harbor received critiques from Balinese society. To connect the two islands by land route would be considered a poor decision since it would affect some values and cultures that the community, especially Bali, holds dearly. Thus as an alternative solution, the idea of making another dock, an executive dock, both in Ketapang and Gilimanuk, is much preferred. The presence of the executive port will automatically eradicate the resurgent discourse on the Java-Bali bridge construction. Because crossing via ship alone takes 15 minutes, thus the Java-Bali bridge seems unnecessary. The executive pier would be in synergy with the construction of the Denpasar - Gilimanuk toll road.